Quality of Handwashing in Informal Workers in Indonesia - Basuki Rachmat; Antonius Yudi Kristanto; Totih Ratna Sondari (JURNAL KESEHATAN LINGKUNGAN, 2022)
Introduction: Worker behavior of handwashing with soap in the informal sector has rarely not been studied in Indonesia. This study was conducted to determine factors related to the quality of handwashing performed by workers in the formal and informal sectors in Indonesia. Methods: The research used secondary data from Indonesia Basic Health Research. The research design was cross-sectional, and a total sample included was 421,404 workers at the productive age of 15-64 years across 34 provinces in Indonesia. The data collected included age, gender, marital status, education, place of residence, occupation, and handwashing practice. The determinants were identified using binary logistic regression. Results and Discussion: Results showed that 1.9% of workers did not wash their hands, and 35.0% only washed their hands with water; most of them worked in the informal sector (77.5%). Regarding the characteristics of workers, age (OR=1.17; 95% CI: 1.14–1.21), gender (OR=1.23; 95% CI: 0.93–0.99), education (OR=2.07; 95% CI: 2.01–2.14), and formal workplace (OR=1.43; 95% CI: 1.40-1.46) were mostly related to the quality of handwashing. Conclusion: The government is expected to formulate a structured policy in educating the workers, especially for male, young (15-24 years), low educated, and informal workers, about good handwashing. This study recommends that the government should use the current research findings to target proper population for the policy implementation.